The relationship between organizational culture and employees' job performance at UiTM Pahang, Jengka Campus / Nurul Nadia Izwani Ahmad - Ahmad, Nurul Nadia Izwani (Faculty of Business and Management, 2018)
This research has been conducted to identify the relationship between organizational culture and employees' job performance at UiTM Pahang, Jengka Campus. This research has four research questions which are the level of overall organizational culture, the organizational culture trait that has the highest level of implementation among employees, the level of overall job performance and the relationship between organizational culture and employees' job performance. The scopes of this research are focused on 60 number of population. The sample sizes taken are 54 people as referred to the sample size for a given population by Krejcie and Morgan (1970). The sampling technique used is simple random sampling. The research findings can be concluded that there is a strong relationship between the four traits of organizational culture and employees' job performance at UiTM Pahang, Jengka Campus.